How do generic statements impact performance? Evidence for entity beliefs. Issue 2 (30th June 2016) - Park, Daeun; Schaeffer, Marjorie W.; Nolla, Kyle M.; Levine, Susan C.; Beilock, Sian L.
Abstract: Generic statements about the abilities of children's social groups (e.g. 'Girls/Boys are good at this game') negatively impact children's performance – even if the statements are favorable towards children's own social groups. We explored the mechanism by which generic language impairs children's performance. Across three studies, our findings suggest that generic statements influence children's performance by creating an entity belief (i.e. a belief that a fixed ability determines performance). Children who were exposed to a generic statement about their social group's ability performed worse than children in control conditions. This effect hurt children's performance even when the person who made the generic statement was no longer present and a new person not privy to the statement replaced them. However, when children heard a generic statement paired with an effort explanation (i.e. 'Girls/Boys are good at this game because they try really hard when they draw') they performed better than children who heard the generic statement with no explanation (i.e. just 'Girls/Boys are good at this game') and children who heard the generic statement paired with a trait explanation (i.e. 'Girls/Boys are good at this game because they are smart and really good at drawing'). This work uncovers when and how generic statements that refer to the ability of one's social group hinder performance, informing the development of practices to improve student motivation and learning. Abstract : Generic statements impair children's performance by creating an entity belief that a fixed ability determines performance. By coupling with generic statements with an effort explanation, the detrimental effects are mitigated. The current work elucidates how and when generic statements about the ability of one's social group hinders performance as well as identifying a way to negate the detrimental effects of such statements.